Diseases of black pepper (Piper nigrum L.) and their management - SARMA, M ANANDARAJ, Y R (Journal of Spices and Aromatic Crops, 1995)
Among the diseases reported on black pepper (Piper nigrum L.), blight, root rot and basal wilt in the nursery; foot rot, slow decline and anthracnose in the field are important. Stunted disease, phyllody and leaf spots are also becoming serious. The symptomatology, causal organisms and control measures of major diseases are outlined in this paper and future lines of work suggested.